KEKUATAN HUKUM AKTA PERDAMAIAN MELALUI PROSES PENGADILAN DAN DILUAR PENGADILAN - Agus Supendi, I Putu; Putrawan, Suatra (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 04, September 2013)
Inclusion of peace procedure into the justice system is based on article 130 HIR/154 RBg which described the judge should encourage litigants to pursue peace procedure beforehand. In article 1851 Code of Civil Law (Civil Code) can be seen that peace has a condition that can be called legitimate, one of which is poured peace results in written form. In article 6 of Law 30 of 1999 on abritase and alternative dispute resolution also called for the terms in the agreement in writing. But a lot of peace that is not poured in written form and not filed in the district court Later very likely arise a problem if one party does not fulfill the promise to implement the contents of the peace so how do the forces of law contained in the decision of whether peace through the court process and how can peace through force of law outside the court process which is not registered in the District Court.
Keywords: Power of Law, Peace Decision, the Court